Analisis Pemanfaatan Media Sosial Facebook sebagai Sumber Informasi dalam Usahatani Komunitas Petani Hidroponik di Kota Kendari - Siti Mei Indahsari; Hartina Batoa; Iskandar Zainuddin Rela (Fakultas Pertanian Universitas Halu Oleo, 2022)
This study aims to determine the use of social media Facebook hydroponic farming community in Kendari City. This research has been conducted on the Hydroponic Farmer Community in Kendari City, Southeast Sulawesi Province. The selection of the research location was done purposively. This research involved 40 hydroponic farmers in Kendari City. The research was carried out in August – October 2021. The types and sources of data used in this study include: primary data and secondary data. The technique in this research is survey, interview. The variables in this research are: Social Media, including: Context, Communication, Collaboration, and Connection. The type of research is quantitative. The first data analysis was conducted to determine the use of social media for hydroponic farming communities in Kendari City and analyzed using quantitative descriptive analysis methods which were processed using class interval formulas. The results showed that the use of Facebook Social Media Hydroponic Farmer Community in Kendari City was high in terms of the use of context, communication, collaboration and even connection. This shows that hydroponic farmers dominate the use of social media facebook as a source of information.